Inovasi Pengolahan Buah Nipah Tua (Nypa fruticans) menjadi Tepung dan Nugget: Pemberdayaan Masyarakat Desa Salo Palai: Innovation in Processing Old Nypa (Nypa fruticans) Fruit into Flour and Nuggets: Empowering the Community of Salo Palai Village - Wahyuni, Leny Eka Tyas; Pijaryani, Indria; Fadilla, Raisa; Anggreini, Putri; Siregar, Vita Olivia; Arief, Maryam Jamila; Nisaa, Nur Rezky Khairun (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Old Nypa fruit (Nypa fruticans) often becomes waste in Salo Palai Village, East Kalimantan, due to a lack of knowledge regarding its utilization. Therefore, this activity aims to empower the community through training on processing old Nypa fruit into flour and nuggets, enhancing economic value, and reducing waste by utilizing local natural resources. The method consists of socialization by an expert speaker followed by a workshop on processing Nypa fruit. The activities were attended by members of the forest farmer group in Salo Palai Village. The outcome of this activity includes the production of Nypa fruit flour and nuggets made from Nypa flour. The results indicate that the residents of Salo Palai Village, particularly the members of the farmer group, are capable of applying information and technology related to processing aged Nypa fruit into flour and nuggets.